Array Non-Stationarity-Aware CP Design in OFDM XL-MIMO Systems - Yahya, Salim M.; Kihero, Abuu B.; Memisoglu, Ebubekir; Arslan, Huseyin (IEEE-Inst Electrical Electronics Engineers Inc, 2025)
The cyclic prefix (CP) is a fundamental feature that enables orthogonal frequency division multiplexing (OFDM) to achieve efficient frequency-domain equalization and resilience against delay spread (DS). However, the trade-off is a reduction in spectral efficiency (SE), prompting the need for methods to minimize CP length without compromising performance. This letter introduces an innovative CP reduction approach leveraging array non-stationarity in extra-large MIMO (XL-MIMO) systems, particularly through the concept of visibility regions (VRs). Unlike conventional methods that adopt a worst-case scenario for CP length, our approach customizes the CP length based on the maximum excess delay of each VRs, thereby reducing the CP overhead. To enhance diversity gain, maximal ratio combining (MRC) is used to optimize the contributions from antenna elements. Simulation results validate our method's ability to improve SE while reducing latency and maintaining low computational complexity. The proposed approach demonstrates practical gains with standard CP configurations, marking a significant step toward more efficient and robust XL-MIMO OFDM systems.
Keywords: Delays; OFDM; Symbols; Vectors; TV; Standards; Noise measurement; Correlation; Spectral efficiency; Signal to noise ratio; CP length reduction; clustered delays; visibility regions; array non-stationarity; XL-MIMO; spectral efficiency; OFDM